2009
DOI: 10.1007/s11269-008-9395-9
|View full text |Cite
|
Sign up to set email alerts
|

Harmonised Principles for Public Participation in Quality Assurance of Integrated Water Resources Modelling

Abstract: The main purpose of public participation in integrated water resources modelling is to improve decision-making by ensuring that decisions are soundly based on shared knowledge, experience and scientific evidence. The present paper describes stakeholder involvement in the modelling process. The point of departure is the guidelines for quality assurance for 'scientific' water resources modelling developed under the EU research project HarmoniQuA, which has developed a computer based Modelling Support Tool (MoST)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…It would "allow for exchanges, co-evolution, and joint construction of knowledge with the aim of enriching decision-making" (Van den Hove 2007). Relations and trust between the actors involved may improve (e.g., Collins and Ison 2010), the credibility of the research results and their relevance for policymaking may increase, and as a result of this appreciation of the research results by authorities and other stakeholders may improve (Lavis et al 2004;Sarewitz and Pielke 2007;Henriksen et al 2009). By enhancing reflection on their own and others' perspectives, collaborative research may also lead to better understanding among the stakeholders of each other's perspective (Habermas 1984;Slavin 1996;Croke et al 2007;Dimadama and Zikos 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It would "allow for exchanges, co-evolution, and joint construction of knowledge with the aim of enriching decision-making" (Van den Hove 2007). Relations and trust between the actors involved may improve (e.g., Collins and Ison 2010), the credibility of the research results and their relevance for policymaking may increase, and as a result of this appreciation of the research results by authorities and other stakeholders may improve (Lavis et al 2004;Sarewitz and Pielke 2007;Henriksen et al 2009). By enhancing reflection on their own and others' perspectives, collaborative research may also lead to better understanding among the stakeholders of each other's perspective (Habermas 1984;Slavin 1996;Croke et al 2007;Dimadama and Zikos 2010).…”
mentioning
confidence: 99%
“…Uptake is more likely when the exchanged knowledge is seen as relevant for the issue at stake (Cash et al 2003;Brugnach et al 2007;Collins and Ison 2010). In addition, the scientific quality and credibility of the knowledge influence learning (Weiss 1977;Cash et al 2003;Brugnach et al 2007;Croke et al 2007;Henriksen et al 2009). Credibility depends to a large extent on the type and authority of the researchers involved.…”
mentioning
confidence: 99%
“…The framework's approach is to use two SD-principles-participation and integration-as the points of departure. These are well-established procedural principles of SD 3 and by far the most cited SD procedural principles recognized in the NRM field (see for example Gregersen et al 2007;Sawhney et al 2007;Henriksen et al 2009). The principles still say little about how to design a planning process, however.…”
Section: The Sustainable Procedures Frameworkmentioning
confidence: 96%
“…Hare (2011) proposed four categories (following the process phases he identified) based on the approach of Bots and van Daalen (2008). The perspective purported by these categorizations is more consistent with the ''truth to power'' idea by participatory methods, indicating that process governance is with the researcher (see also Henriksen et al 2009). Barreteau et al (2013) identified three basic expectations (as they called it) of participatory approaches in modeling.…”
Section: Functional-dynamic Perspective On Participatory Processesmentioning
confidence: 97%